Analisis de la produccion bananera pre y pos pandemia de la “asociacion asocobaoro” periodo 2019-2020 - Apolo Aguilar, Dalton Alexander (Machala : Universidad Técnica de Machala, 2021)
Bananas occupy the fourth position as the most important food on the planet, where Ecuador stands out as one of the main exporters, occupying 29% of the market. In Ecuador, the province of El Oro has the largest number of banana farms nationwide, which occupies 41% of the total. This study was developed in the association "ASOCOBAORO" located in the Machala canton of the El Oro province, with the objective of analyzing the pre and post pandemic banana production within the 2019-2020 periods by analyzing the production data of both years. For this, a descriptive, non-experimental, cross-sectional methodological design was used to collect information on banana production in the pre- and post-pandemic period without manipulating any study variable. The main results obtained were that the association suffered an economic impact due to the pandemic, where in 2020 the income and registered production volume were lower than in 2019, in addition to taking measures such as teleworking, reduction of working hours and termination of contracts, this due to the fact that most of the members of the association could not keep their payroll for more than 9 weeks.
El banano ocupa la posición número cuatro como alimento más importante en el planeta, en donde Ecuador destaca como uno de los principales exportadores ocupando el 29% del mercado. En Ecuador la provincia de El Oro cuenta con la mayor cantidad de haciendas bananera a escala nacional, la misma que ocupa el 41% del total. El presente estudio se desarrolló en la asociación “ASOCOBAORO” ubicada en el cantón Machala de la provincia de El Oro, con el objetivo de analizar la producción bananera pre y post pandemia dentro de los periodos 2019-2020 mediante el análisis de los datos productivos de ambos años. Para ello se utilizó un diseño metodológico descriptivo, no experimental de corte transversal que permitió recabar información de la producción bananera del periodo pre y post pandemia sin manipular ninguna variable de estudio. Los principales resultados obtenidos fueron que la asociación sufrió una afectación económica debido al pandemia, en donde en el año 2020 los ingresos y volumen de producción registrado fueron inferiores a los del año 2019, además de tomar medidas como teletrabajo, reducción de horario laboral y terminación de contratos, esto debido a que la mayoría de los socios de la asociación no lograron mantener su nómina por más de 9 semanas.
Keywords: PANDEMIA; EXPORTACIONES; INGRESOS; BANANO